Validity and Reliability of the Artificial Intelligence Literacy Instrument for Prospective Islamic Education Teachers: A Rasch Analysis - Sari, Herlini Puspika; arisanti, devi; ilhami, Aldeva; Salman, Nola Fibriyani Bte; Faizah, Ulfa (POTENSIA: Jurnal Kependidikan Islam, 2025)
This study aims to validate an Artificial Intelligence (AI) literacy instrument for Islamic Education (PAI) students using Rasch analysis to evaluate its reliability, validity, item-fit statistics, and unidimensionality. The instrument was developed to measure the extent of AI literacy among prospective Islamic Education teachers. A cross-sectional survey design was employed, involving 64 students from a university in Riau, Indonesia. Participants completed an AI literacy instrument consisting of 85 items. The sampling technique used was quota sampling. Data were analyzed using the Rasch model with the aid of Winsteps software version 3.73. The results of the Rasch analysis indicated that the instrument demonstrated good reliability (α = 0.85), excellent item quality (0.94), and consistent respondent reliability (0.84). In terms of validity, the three dimensions of AI literacy were confirmed to possess unidimensional properties. The practical implication of this study lies in providing higher education institutions with a validated AI literacy instrument that can be used to assess the knowledge of future Islamic Education teachers. By employing Rasch analysis, this study contributes to enhancing the psychometric robustness of measurement tools, particularly in the context of assessing artificial intelligence literacy in Indonesia.